Selection of Shipping Container Vendors Using Analytical Hierarchy Process (AHP) - Muhammad Jumandono; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2019)
This research was conducted on a service company in Surabaya engaged in forwarder/ logistic using containers. Customers from this company spread in East Java, such as Surabaya, Sidoarjo, Gresik, and Mojokerto. The chosen export destination is exporting to the Middle East, such as Saudi Arabia and Qatar. The problem faced by the company is the selection of container vendors for shipping exports to the Middle East. There are 3 shipping container vendors that are often used for shipping to the Middle East, namely vendors A, B, dan C. This research uses the FGD method and Analytical Hierarchy Process (AHP) method. The FGD method is a method used to find answers to each problem through expert forums or discussion groups. This method will produce relevant criteria. This FGD method will be combined with the AHP method which has a good structure. This is evidenced by the matrices produced until a consistency test. AHP method can solve problems that have multi-criteria up to sub-criteria. Systematic criteria assessment with the first rank in a row until the last rank is the Quality (22.6%), Cost (22.4%), Time (18.3%), Bankruptcy (7.6%), Long-term Cooperation (6.9%), Order Fulfillment (6.1%), Company Profile (5.6%), Standard and Environmental Certification (5.4%), and Exploitation Contract (5.1%). The chosen vendor is vendor B has the highest priority (36.8%), then followed by vendor A is ranked second (33.9%), and the last is vendor C (29.3%)